Dynamics of Indonesian and Malaysian Education Management - Rosida, Rosida; Mustiningsih, Mustiningsih (Universitas Negeri Malang, 2024)
A comparative study of Indonesian and Malaysian education management shows that there are significant similarities and differences. Both countries have a common goal of improving the quality of education, but the approaches used are different. Indonesia tends to be more decentralized with a flexible curriculum and high community participation, while Malaysia is more centralized with a structured curriculum. Both have adopted various innovations in education, but still face similar challenges such as equalizing quality and increasing teacher competency. This study concludes that understanding the differences and similarities between the two systems can provide valuable input for developing education policies in each country.